Avaliação dos efeitos da aplicação de fertilizante organomineral bioativado na cultura da soja - Santos, Tatiane Barbosa dos (2022)
Soybean culture has great representation in the world agricultural scenario, and the focus of research is the development of new technologies that make production more efficient and sustainable. Fertilization plays a fundamental role in plant development, as it provides nutrients in adequate amounts for the plant to grow and reach the reproductive stage for grain formation with the expected quality and quantity. In this context, obtaining the maximum performance of a cultivar through the use of renewable resources in fertilization, through the use of waste, and consequent reduction in the import of raw materials for the production of chemical fertilizers, has been considered a viable and sustainable alternative in the long term. . Among the options, organomineral fertilizers from the association between mineral fertilizers and organic compounds can be used more efficiently by the plant, minimizing the effects of water deficit due to organic matter and microorganisms present in it. They can also be optimized by the addition of microorganisms known for their functions as plant growth promoters, giving rise to a bioactivated product. Thus, the objective of this work was to evaluate the effects of bioactivated organomineral fertilizer on plant development and productivity of soybean crops compared to traditional mineral fertilizer. The following were evaluated: plant height (cm), stem diameter (mm), number of branches, number of pods, weight of 1000 grains (g) and productivity (kg ha-1) per area. Soil chemical analyzes were also carried out, seeking to evaluate the effect of fertilization at the end of the crop cultivation cycle. Still, NDVI images were obtained to compare the soybean crop in different phenological stages of development. Significant differences were observed between treatments in the evaluations of plant height (cm), stem diameter (mm), 1000 grain mass (g) and productivity (kg ha-1), and the treatment with organomineral fertilizer generated increments of 8.38%, 9.40%, 7.74% and 10.80% for each of the attributes, respectively. There was an increase in soil pH, which, aided by the action of microorganisms, increased phosphorus levels, stimulating plant development. The water deficit caused a drop of 85.95% in the productivity of the culture, confirmed with the use of NDVI images, where it is possible to observe the closing of the stomata at 55 DAS and the beginning of early senescence at 85 DAS. Thus, despite all the water deficit suffered by the culture, the organomineral fertilizer managed to achieve better performance, producing an average of 0.54 bags more than the mineral fertilizer in the first application cycle.